2021
DOI: 10.3390/ani11092598
|View full text |Cite
|
Sign up to set email alerts
|

Toward Precise Nutrient Value of Feed in Growing Pigs: Effect of Meal Size, Frequency and Dietary Fibre on Nutrient Utilisation

Abstract: Nutritional values of ingredients have been and still are the subject of many studies to reduce security margins of nutrients when formulating diets to reduce feed cost. In most studies, pigs are fed a limited amount of feed in a limited number of meals that do not represent how pigs are fed in commercial farm conditions. With free access to feed, pigs follow their intrinsic feeding behaviour. Feed intake is regulated by satiety and satiation signals. Reducing the feed intake level or feeding frequency can aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…Increasing insoluble fiber in the diet decreases the mean retention time in the small and large intestine of pigs ( Wilfart et al., 2007 ). The increased DM intake causes a large volume of intestinal contents, which can exert a direct physical action on the intestine and thus stimulate gastrointestinal transit ( Chasse et al., 2021 ). In addition, high chyme viscosity due to soluble fiber hinders contact between chyme and digestive enzymes ( Gutierrez et al., 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing insoluble fiber in the diet decreases the mean retention time in the small and large intestine of pigs ( Wilfart et al., 2007 ). The increased DM intake causes a large volume of intestinal contents, which can exert a direct physical action on the intestine and thus stimulate gastrointestinal transit ( Chasse et al., 2021 ). In addition, high chyme viscosity due to soluble fiber hinders contact between chyme and digestive enzymes ( Gutierrez et al., 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action of an enzyme combination (amylase, xylanase, β-glucanase, lipase, cellulase, β-mannanase phytase, and pectinase) may drive substrate availability for bacterial growth changes [40]. This combination of enzymes may result in a reduction in gut viscosity and nutrient caging with long fiber chains, as well as large and nonadherent layers, resulting in increased nutrient uptake across the gut barrier [41]. This is in line with observations made by Kim et al [42], who observed increased VH and VH/CD and decreased CD in pigs fed an SBM-based diet supplemented with a 0.1% enzyme combination containing amylase, proteinase, phytase, mannanase, and xylanase.…”
Section: Discussionmentioning
confidence: 99%
“…Many alternative feed materials contain more fibre than the traditional feed stock they replace; therefore, their inclusion increases the amount of dietary fibre [ 12 , 13 ]. Increased dietary fibre is a concern because the ability of young pigs to digest fibre is limited [ 14 , 15 ]. Sugar beet pulp (SBP), which is the co-product of sugar beet processing, with a global production of up to 189 mln tons in 2021/2022, is a fibre-rich feed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%